NMDA Receptors Contribute to Retrograde Synaptic Transmission from Ganglion Cell Photoreceptors to Dopaminergic Amacrine Cells - Liu, Lei-Lei; Spix, Nathan J.; Zhang, Dao-Qi (Frontiers in Cellular Neuroscience, 2017)
Recently, a line of evidence has demonstrated that the vertebrate retina possesses a novel retrograde signalling pathway. In this pathway, phototransduction is initiated by the photopigment melanopsin, which is expressed in a small population of retinal ganglion cells. These ganglion cell photoreceptors then signal to dopaminergic amacrine cells (DACs) through glutamatergic synapses, influencing visual light adaptation. We have previously demonstrated that in Mg2+-containing solution, AMPA receptors mediate this glutamatergic transmission. Here, we demonstrate that removing extracellular Mg2+ enhances melanopsin-based DAC light responses at membrane potentials more negative than -40 mV. Melanopsin-based responses in Mg2+-free solution were profoundly suppressed by the selective NMDA receptor antagonist D-AP5. In addition, application of NMDA to the retina produced excitatory inward currents in DACs. These data strongly suggest that DACs express functional NMDA receptors. We further found that in the presence of Mg2+, D-AP5 reduced the peak amplitude of melanopsin-based DAC responses by ~70% when the cells were held at their resting membrane potential (-50 mV), indicating that NMDA receptors are likely to contribute to retrograde signal transmission to DACs under physiological conditions. Moreover, our data show that melanopsin-based NMDA-receptor-mediated responses in DACs are suppressed by antagonists specific to either the NR2A or NR2B receptor subtype. Immunohistochemical results show that NR2A and NR2B subunits are expressed on DAC somata and processes. These results suggest that DACs express functional NMDA receptors containing both NR2A and NR2B subunits. Collectively, our data reveal that, along with AMPA receptors, NR2A- and NR2B-containing NMDA receptors mediate retrograde signal transmission from ganglion cell photoreceptors to DACs.